2004
DOI: 10.1023/b:biop.0000024295.27419.89
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium-Induced Changes in Chloroplast Lipids and Photosystem Activities in Barley Plants

Abstract: Fatty acid content and composition of chloroplast membranes, ethylene production associated with thylakoid lipids degradation as well as photosynthetic electron transport involving photosystems 1 and 2 were used to determine the effects of increasing Cd concentrations in the growth medium [0, 14, 28, and 42 mg(Cd) kg -1 (sand)] on the photosynthetic performance of barley plants (H. vulgare L., cv. CE9704). High concentrations of Cd triggered serious disturbances of the chloroplast membranes. Ethylene productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(58 citation statements)
references
References 22 publications
4
49
0
4
Order By: Relevance
“…In recent studies, increased lipid peroxidation has been observed in plants under heavy metal stress, such as tomato (Krupa & Baszynski 1985;Quariti et al 1997;Ben Ammar et al 2005), wheat (Malik et al 1992), barley (Vassilev 2004), and mustard (Gaur & Grupa 1994;Nouairi et al 2006). Results of the current study indicate that MDA content substantially increased with all concentrations of Pb +2 contamination.…”
Section: +2supporting
confidence: 58%
“…In recent studies, increased lipid peroxidation has been observed in plants under heavy metal stress, such as tomato (Krupa & Baszynski 1985;Quariti et al 1997;Ben Ammar et al 2005), wheat (Malik et al 1992), barley (Vassilev 2004), and mustard (Gaur & Grupa 1994;Nouairi et al 2006). Results of the current study indicate that MDA content substantially increased with all concentrations of Pb +2 contamination.…”
Section: +2supporting
confidence: 58%
“…Therefore, the exposure of heavy metals might not affect photosynthesis as quickly as it does growth, as was shown in exposure experiments of Cu and Cr. Cu 2+ can oxidize membrane lipids, resulting in an increased quantity of active oxygen which can break the thylakoid layer structure, thus affecting photosynthesis of the plant [15,16]. The results showed that photosynthesis rates remained at normal levels longer than growth rates did under the stress of Cu 2+ .…”
Section: Comparison Of the Effects On The Growth And Photosynthesismentioning
confidence: 99%
“…For instance, Cd not only inhibits growth (Lunáčková et al 2003, Dong et al 2005), but also brings about changes in various physiological and biochemical characteristics such as water balance, nutrient uptake (Vassilev et al 1997, Dražić et al 2006, Scebba et al 2006) and photosynthetic electron transport around photosystems PS I and PS II (Siedlecka and Baszynski 1993, Skórzyńska-Polit and Baszynski 1995, Vassilev et al 2004. Similarly, Cr inhibits electron transport, reduces CO 2 fixation, chloroplast disorganization (Zeid 2001;Davies et al 2002;Shanker 2003), decreases water potential, increases transpiration rate, reduces diffusive resistance, and causes a reduction in tracheary vessel diameter (Vazques et al 1987).…”
Section: Effect On Plant Physiologymentioning
confidence: 99%